2021
DOI: 10.3390/biom12010034
|View full text |Cite
|
Sign up to set email alerts
|

RTP801/REDD1 Is Involved in Neuroinflammation and Modulates Cognitive Dysfunction in Huntington’s Disease

Abstract: RTP801/REDD1 is a stress-regulated protein whose levels are increased in several neurodegenerative diseases such as Parkinson’s, Alzheimer’s, and Huntington’s diseases (HD). RTP801 downregulation ameliorates behavioral abnormalities in several mouse models of these disorders. In HD, RTP801 mediates mutant huntingtin (mhtt) toxicity in in vitro models and its levels are increased in human iPSCs, human postmortem putamen samples, and in striatal synaptosomes from mouse models of the disease. Here, we investigate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 80 publications
1
8
0
Order By: Relevance
“…In line with this, downregulation of RTP801 in AD and HD mouse models prevents cognitive de cits and neuroin ammation 45,50 .…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…In line with this, downregulation of RTP801 in AD and HD mouse models prevents cognitive de cits and neuroin ammation 45,50 .…”
Section: Introductionsupporting
confidence: 54%
“…Dendritic branching defects in mature neurons have devastating consequences on neuronal function and survival and are common features in patients suffering from neurodegenerative diseases 145 . The fact that increased levels of RTP801 are found in PD, AD and HD human postmortem brains, and contribute to neuron impairment in disease mouse models 45,50 , suggests that RTP801 could be an active player in spreading neurodegeneration via EVs and therefore, a potential future target in the treatment of neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of REDD1 is altered in a vast range of pathologies, from inflammatory diseases to cancer and neurodegenerative disorders. For instance, we have described that REDD1 is upregulated in postmortem brains of patients with Parkinson's (PD) [9], Huntington's (HD) [15] and AD [16], and it has been linked to increased neuroinflammation and cognitive deficits in both HD [17] and AD [16] mice models. Interestingly, selective knockdown of REDD1 in hippocampal neurons with shRNA‐containing AAV particles ameliorates cognitive deficits as well as diminishes astrocytes‐ and microglia‐mediated neuroinflammation in a murine model of HD [16] and AD [15].…”
Section: Redd1 Role In Physiological and Pathological Conditionsmentioning
confidence: 99%
“…DNA damage-inducible transcript 4 (DDIT4) is an evolutionarily conserved protein that has low expression under basal conditions, but is overexpressed when cells are stimulated by oxidative stress, endoplasmic reticulum stress, and hypoxia. 10 , 11 Subsequent independent studies have reported that DDIT4 is involved in various diseases, including Alzheimer’s disease and Parkinson’s disease, 12 myocardial ischaemia/reperfusion injury, 13 and osteoarthritis. 14 Nevertheless, the role of DDIT4 in IVDD warrants further exploration.…”
Section: Introductionmentioning
confidence: 99%